Optimalisasi Produksi Pelet Ikan Berbahan Limbah Organik melalui Otomatisasi di Pokdakan MCS - Eny Boedi Orbawati; Ari Mukti; Eric Armando; Fadlurrahman, Fadlurrahman; Ikhtiara, Seiren (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Mina Cikal Sari group is a fish farming group that faces several problems including fish feed production, product packaging and product packaging. So far, to meet fish feed needs by making conventional feed and buying feed at a more expensive cost. Apart from that, product marketing also experienced problems due to inadequate packaging. The service method is carried out through several stages, namely socialization, feed formulation training, training in the application of alternative pellet production technology, digital marketing training, and product packaging training. The results of this service include increasing partner understanding, increasing pellet production, and increasing production of seasoned tilapia products.